Systematic overview of economic evaluations of health-related rehabilitation. Issue 1 (January 2016) - Howard-Wilsher, Stephanie; Irvine, Lisa; Fan, Hong; Shakespeare, Tom; Suhrcke, Marc; Horton, Simon; Poland, Fiona; Hooper, Lee; Song, Fujian
Abstract: Background: Health related rehabilitation is instrumental in improving functioning and promoting participation by people with disabilities. To make clinical and policy decisions about health-related rehabilitation, resource allocation and cost issues need to be considered. Objectives: To provide an overview of systematic reviews (SRs) on economic evaluations of health-related rehabilitation. Methods: We searched multiple databases to identify relevant SRs of economic evaluations of health-related rehabilitation. Review quality was assessed by AMSTAR checklist. Results: We included 64 SRs, most of which included economic evaluations alongside randomized controlled trials (RCTs). The review quality was low to moderate (AMSTAR score 5–8) in 35, and high (score 9–11) in 29 of the included SRs. The included SRs addressed various health conditions, including spinal or other pain conditions ( n  = 14), age-related problems (11), stroke (7), musculoskeletal disorders (6), heart diseases (4), pulmonary (3), mental health problems (3), and injury (3). Physiotherapy was the most commonly evaluated rehabilitation intervention in the included SRs ( n  = 24). Other commonly evaluated interventions included multidisciplinary programmes (14); behavioral, educational or psychological interventions (11); home-based interventions (11); complementary therapy (6); self-management (6); and occupational therapy (4). Conclusions: Although the available evidence is often described as limited, inconsistent or inconclusive, some rehabilitation interventions were cost-effective or showed cost-saving in a variety of disability conditions. Available evidence comes predominantly from high income countries, therefore economic evaluations of health-related rehabilitation are urgently required in less resourced settings.